Frequência de Obesidade e Risco Cardiometabólico em escolares de cinco a 10 anos de idade na região Oeste do Paraná - Oliveira, Maria de Fatima de (2019)
Childhood obesity can trigger metabolic changes and predispose to the early development of chronic degenerative diseases such as diabetes mellitus type 2 (DM2) and cardiovascular disease (CVD). Obese children and adolescents may have visceral obesity, insulin resistance (IR), hyperglycemia, dyslipidemia, and hypertension; picture similar to the metabolic syndrome (MS) typical of obese adults. There is no consensus on the diagnosis of MS in children under 10 years. The aim of the present study was to investigate the prevalence of obesity, as well as to identify predictors of cardiometabolic risk (CMR) among male and female students, aged from five to 10 years, in the belonging to two municipal schools in the western region of the state of Paraná. The aim of the present study was to investigate the prevalence of obesity, as well as to identify predictors of cardiometabolic risk (CMR) among male and female students, aged from five to 10 years, in the belonging to two municipal schools in the western region of the state of Paraná. Therefor, a quantitative approach study with cross-sectional design was performed.Which were cikkected body weight (Kg), height (m²), to calculate Body Mass Index (BMI). Mensured of the abdominal circumference (AC), as well as the systolic (SBP), diastolic (SBP) blood pressure (BP) and it was recorded heart rate (HR). With the aid of test strips and electronic reading equipment, the values of glucose, triglycerides and total cholesterol (mg/dL) were measured in a capillary blood sample. The presence of obesity (AC>P90) associated with two more altered measures of: SBP> P90; blood glucose>100mg/dL; triglycerides>101mg/dL; or total cholesterol>140mg/ dL was considered as CMR. The data are presented as mean ± standard deviation (SD) or frequency, assessed by Chi-square test. Binary logistic regression and Odds Ratio (OR) calculation were performed to evaluate CMR (p<0.05). A total of 513 students were evaluated, 21-25% had above normal AC and SBP values (P>90-95) and 30-35% for DBP. The highest frequency of underweight and obese was among boys and eutrophic in girls (p<0.05). Students with above-normal SBP are 544.783 times more likely to have CMR (OR = 544.783; 95% CI: 19.738 - 15036.412). The same pattern was found for individuals with above-normal DBP, 314,022 times more likely to have CMR (OR = 314,022; 95% CI: 10,621- 9284,304). Although CMR was similar between genders, there is a significant presence of obesity, changes in BP, triglycerides and total cholesterol among students, which exposes them to a higher risk of developing MS in adulthood age and to become part of the group. of adults with chronic health conditions.